THE INFLUENCE OF THE BRAND IMAGE, THE QUALITY PRODUCT, AND CUSTOMER SATISFACTION ON REPURCHASING INTEREST IN SMALL AND MEDIUM BUSINESS SHOPS OF TRADITIONAL PRODUCTS IN SERANG - Hamdan Hamdan (Yayasan Education and Social Center, 2022)
The purpose of this study was to examine the effect of Brand Image on repurchase intention, to test the effect of Product Quality on repurchase intention, to test the effect of Customer Satisfaction on repurchase intention, and to test the effect of Brand Image, Product Quality, Customer Satisfaction on repurchase interest. In Small and Medium Business Stores of Traditional Products in Serang, This research uses an explanatory quantitative approach. The number of samples in this study was 85 respondents. The results of this study in hypothesis 1 obtained the results tcount > t-table (2,362 > 1,989) with a significance level of 0.02 (0.02 < 0.05) Hypothesis 2 obtained the results tcount > t-table (2.398 > 1.899) with a significance level of 0.02 (0.02 < 0.05). Hypothesis 3 obtained the results of tcount > t-table (2,659 > 1,989) with a significance level of 0.01 (0.01 < 0.05). Hypothesis 4 obtained the results Fcount > Ftable (7.566 > 2.717) with a significance level of 0.00 (0.00 < 0.05), which means that there is a significant influence between brand image, product quality, and customer satisfaction. The conclusion of this study on hypothesis 1 to hypothesis 4 is that there is a significant influence on the purchase intention of Small and Medium Enterprises Traditional Products in Serang City